Structure of Teacher Education - Craig, Cheryl J. (International Handbook of Teacher Education, 2016)
This chapter defines the structure of teacher education and offers a sampling of how teacher education programmes are organized in over 50 nations around the world. Individual country profiles include information about selected nations’ cultural, economic and political systems as well as teacher education programme types. The work also examines how teacher education is organized internally within universities (University of Bergen, Norway) and how external governing bodies (i.e., Houston, TX, USA) may authorize multiple teacher education providers, each offerings its own version of teacher education, and each reflecting its own unique structure. The work conclusively shows that the structure of education is not only shaped by history and culture, but increasingly dictated by politics as multiple countries’ profiles repeatedly demonstrate.